Foreign Remittance Income in Bangladesh: Opportunities and Challenges - Rahim, Sheikh Abdur; Alam, Md. Asraful (Asian Business Review, 2013)
A remittance is a transfer of money by a foreign worker to his or her home country. Remittance can also refer to the accounting concept of a monetary payment transferred by a customer to a business (Wikipedia, the free encyclopedia). Remittances have been playing a very significant role for the overall economic development of Bangladesh. Therefore, this paper attempts to explore the actual remittance income and its impact on overall economy of Bangladesh. Recently, the world has suffering from the global financial crisis. That is why, the job opportunities are shrinking drastically for the last couple of years. As a result, the government of Bangladesh is now facing tremendous challenges to send people abroad for employment. Thus, this paper also attempts to clearly articulate the opportunities and challenges of remittance income in Bangladesh and suggested some possible courses of action to face these challenges with smart at hand.